EVALUATION OF ROAD GEOMETRY TO TOURISM AREAS (CASE STUDY: EAST RING ROAD - JATIGEDE DAM, SUMEDANG - INDONESIA) - Nina Rifka Puspitasari; Mulia Pamadi; Adinda Fajarika (LEADER: Civil Engineering and Architecture Journal, 2024)
Road geometry design is a method of planning roads geometrically or involving the computation a angles through a process. For roads geometric design, it is necessary to assess the suitability of design criteria with applicable guidelines, namely the Road Geometric Design Guidelines. Therefore, this study will conduct a geometric design assessment of application of the existing road geometric design of the Jatigede East Ring Roads, and adjust it to the "Road Geometric Design Guidelines". The research method used in this research is the evaluation research method of the research object, namely the Jatigede East Ring Road Section is the road to the Jatigede Dam tourist area which is not by the road geometry standards. It has a sharp bend less than Rmin = 110, which the 1997 highway requirement for collection roads with Vr = 60 km/h. Such road conditions can cause insecurity and discomfort for road users. Therefore, the authors conducted research with the title "Case Study of Road Geometry Evaluation Towards Tourism Area Case Study: East Ring - Jatigede Dam, Sumedang - Indonesia" Geometry improvements are because many angles are not suitable. To obtain geometry data in the field using Google Earth and Global Mapper, the measured data is coordinate data and elevation data, then using Microsoft Excel to process the measurement results and input them into the Autocad program. Based on the results drawn, geometric analysis. Conducted from 32 corners obtained from the research, only 17 corners with a radius of 115 m meet the criteria. The other 31 turns have radii smaller than the minimum radius, which is quite dangerous for a speed of 60 km/hour. There are steep descents and climbs in some locations, with 28% of the road having a slope much greater than the maximum requirement of 8%.